Empathy at the heart of customer experience: A holistic framework for understanding and enhancing consumer empathy through the lens of customer experience - Leon Lehnert; Christina Kuehnl (Psychology & Marketing, 2024)
Abstract Serving as a social glue in interactions, consumer empathy takes center stage in shaping a pleasant customer experience. Our holistic framework of an empathic customer experience, rooted in the perception–action model of empathy and established customer experience conceptualizations, unveils the close interrelationship between consumer empathy and customer experiences. Grounded in a systematic literature review and a conceptual synthesis, our study contributes to customer experience research by conceptualizing consumer empathy as a cognitive and affective customer experience response, potentially accompanied by supplementary customer experience responses, which we refer to as an empathic customer experience. This study advances empathy literature by offering a systematic overview of an empathic customer experience, covering stimuli at touchpoints that induce an empathic customer experience during consumer interactions, potential contextual factors, and evaluative outcomes of an empathic customer experience. From our results, we derive an agenda with several research directions for the joint investigation of consumer empathy and customer experience to contribute to both research fields. In addition, our framework provides insights for managers, including recommendations for designing stimuli to evoke an empathic customer experience.
Keywords: 330; consumer empathy; customer experience; empathic customer experience framework; perception–action model of empathy